Crystal structure and interaction studies of human DHTKD1 provide insight into a mitochondrial megacomplex in lysine catabolism. (2020) - Bezerra, Gustavo A.; Foster, William R.; Bailey, Henry J.; Hicks, Kevin G.; Sauer, Sven W.; Dimitrov, Bianca
No abstract available